Identifying Cognitive Conflict in Junior High School Students: An Exploratory Case Study on Pythagorean Theorem Problem Solving - Rahayu, Siti Tri; Maulidiya, Della; Utari, Tria; Lestary, Ratnah (Universitas Islam Negeri Sunan Kudus, 2026)
Learning difficulties experienced by students in geometry, particularly with the Pythagorean Theorem, often stem from deep-seated misconceptions and epistemological resistance to new information. Addressing students' misconceptions begins with a deep understanding of the cognitive conflicts they are experiencing. Identifying these conflict mechanisms is an initial diagnostic step for designing effective and sustainable learning strategies. This study aims to deeply describe how specific misconceptions in the Pythagorean Theorem trigger cognitive conflict types (Type I, Type II, and Type III) in students. The research used a descriptive qualitative approach with exploratory case study type. The research subjects were six students from 28 grade IX students at SMPN 11 Bengkulu City, who were then analysed through written tests, observation of physical symptoms (video recordings), and semi-structured interviews. The research findings identified that all types of cognitive conflict appeared in the subjects. Type I Conflict (Initial Concept vs. New Environment) is triggered by the inability to model the geometric decomposition problem and the misidentification of the hypotenuse, resulting in anomalous outcomes that challenge students' initial beliefs. Type II Conflict (New Concept vs Old Environment/Habits) arises when an incorrect procedural schema (R1) is maintained despite the student's potential to activate the correct concept (C2). Meanwhile, Type III Conflict (Initial Concept vs New Concept) is internal, dominant in problems involving special triangle ratios, and signifies a conflict between the dominant general Pythagorean schema and the specific ratio schema that has not yet been stably assimilated. This research underscores the importance of learning strategies in a planned manner that can eliminate the cognitive conflict through instructional design, followed by strong visual scaffolding, to facilitate stable conceptual accommodation. Hambatan belajar yang dialami siswa dalam geometri, khususnya Teorema Pythagoras, seringkali bersumber dari miskonsepsi yang mendalam dan resistensi epistemologi terhadap informasi baru. Penanganan miskonsepsi peserta didik diawali dengan pemahaman mendalam terhadap konflik kognitif yang mereka alami. Identifikasi mekanisme konflik tersebut merupakan tahap diagnostik awal untuk merancang strategi pembelajaran yang efektif dan berkelanjutan. Penelitian ini bertujuan untuk mendeskripsikan secara mendalam bagaimana miskonsepsi spesifik dalam Teorema Pythagoras memicu tipe-tipe konflik kognitif (Tipe I, Tipe II, dan Tipe III) pada siswa. Penelitian menggunakan pendekatan kualitatif deskriptif dengan jenis Studi Kasus Eksploratori. Subjek penelitian dipilih sebanyak enam siswa dari 28 peserta didik kelas IX di SMPN 11 Kota Bengkulu, yang kemudian dianalisis melalui tes tertulis, observasi gejala fisik (rekaman video), dan wawancara semi-terstruktur. Hasil penelitian mengidentifikasi bahwa semua tipe konflik kognitif muncul pada subjek. Konflik Tipe I (Konsep Awal vs Lingkungan Baru) dipicu oleh ketidakmampuan memodelkan masalah dekomposisi geometris dan misidentifikasi hipotenusa, menghasilkan hasil anomali yang menantang keyakinan awal siswa. Konflik Tipe II (Konsep Baru vs Lingkungan Lama/Kebiasaan) muncul ketika skema prosedural yang salah (R1) dipertahankan meskipun siswa memiliki potensi untuk mengaktifkan konsep yang benar (C2). Sementara itu, Konflik Tipe III (Konsep Awal vs Konsep Baru) bersifat internal, dominan pada masalah rasio segitiga istimewa, menandakan pertentangan antara skema umum Pythagoras yang dominan dengan skema rasio spesifik yang belum terasimilasi secara stabil. Penelitian ini menggarisbawahi pentingnya strategi pembelajaran secara terencana yang dapat menekan konflik kognitif melalui desain instruksional, diikuti dengan scaffolding visual yang kuat, untuk memfasilitasi akomodasi konseptual yang stabil.